2018
DOI: 10.3390/molecules23112950
|View full text |Cite
|
Sign up to set email alerts
|

Flubendiamide Enhances Adipogenesis and Inhibits AMPKα in 3T3-L1 Adipocytes

Abstract: Flubendiamide, a ryanoid class insecticide, is widely used in agriculture. Several insecticides have been reported to promote adipogenesis. However, the potential influence of flubendiamide on adipogenesis is largely unknown. The current study was therefore to determine the effects of flubendiamide on adipogenesis utilizing the 3T3-L1 adipocytes model. Flubendiamide treatment not only enhanced triglyceride content in 3T3-L1 adipocytes, but also increased the expression of cytosine-cytosine-adenosine-adenosine-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 30 publications
3
8
0
Order By: Relevance
“…The results of this study showed increased ROS levels and decreased GSH content and reduction in the activities of SOD and GST while increase in GPx activity. Present ndings are in line with the previous toxicity studies of copper and copper nanoparticles 84,85,67,77,72 and ubendiamide toxicity studies [86][87][88] in liver and kidneys.…”
Section: Discussionsupporting
confidence: 92%
“…The results of this study showed increased ROS levels and decreased GSH content and reduction in the activities of SOD and GST while increase in GPx activity. Present ndings are in line with the previous toxicity studies of copper and copper nanoparticles 84,85,67,77,72 and ubendiamide toxicity studies [86][87][88] in liver and kidneys.…”
Section: Discussionsupporting
confidence: 92%
“…It was observed via the activation of AMPK (adenosine monophosphate-activated protein kinase) that curcumin impeded the synthesis of glycerol lipids by hindering the activity of (GPAT-1) glycerol-3-phosphate acyl transferase-1, which in turn esterifies fatty acids into glycerol to form triglycerides for storage [93]. Peng et al as well affirmed in recent research that vitexin, i.e., a flavonoid glycoside (an apigenin-8-C-glucoside), activated AMPKα, which is a key enzyme in controlling and reducing fat accumulation [94][95][96]. Other animal and cell culture studies revealed that the addition of a phenolic compound (resveratrol) to rat isolated hepatocytes turns to hinder the synthesis of triglycerides and fatty acid, i.e., through the lowering effect of lipids.…”
Section: Influence On Lipidsmentioning
confidence: 99%
“…The method for culture 3T3-L1 preadipocytes was determine based on previous studies ( 9 , 16 ). 3T3-L1 preadipocytes were maintained at 37°C in a carbon dioxide incubator in DMEM containing 10% FBS.…”
Section: Methodsmentioning
confidence: 99%
“…More and more studies are reporting the potential link between pesticides exposure and obesity (9)(10)(11)(12)(13)(14)(15)(16)(17)(18). Our previous study has shown that chlorantraniliprole may enhance adipogenesis in 3T3-L1 adipocytes through inhibiting AMPK (19).…”
Section: Introductionmentioning
confidence: 99%